METODE PEMBELAJARAN KOOPERATIF MODEL STAD DAPAT MENINGKATKAN PRESTASI BELAJAR SISWA TERHADAP MOTIVASI BELAJAR PKn PADA SISWA KELAS IV SDN 013 TAMBUSAI UTARA - SYAIFUL MUNAWAR (STKIP ROKANIA, 2019)
This study aims to improve Civics learning outcomeswith the STAD type cooperative learning method forfourth grade students at SDN 013 Tambusai Utara.From the results of the analysis it was found thatstudent achievement improved from cycle I to cycle III,namely cycle I (68.42%) , cycle II (81.58%), cycle III(94.74%).The conclusions of this study are that cooperativelearning methods can positively influence theachievement and learning motivation of fourth gradestudents at SD Negeri 013 Tambusai and this learningmodel can be used as an alternative to PKn learning.